PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAKAN KEKERASAN DI SEKOLAH - Wahyudi; Berliani, Lhatifah; Amelia (JURNAL HUKUM DAS SOLLEN, 2023)
The issue of violence against children in educational institutions is a grave concern, with detrimental impacts on both the physical and psychological health of children, as well as their fundamental rights. This research explores the legal aspects related to child protection in the school environment, with a focus on legal measures that can be used to prevent, address, and punish perpetrators of violence based on Law No. 35 of 2014 about Child Protection, including potential obstacles that may arise in its implementation. The research employs a juridical analysis approach Through the gathering of information from diverse outlets, including legal texts and literature, relevant government policies, and data from real cases related to child protection in schools. The research findings indicate that despite the existence of a substantial policy framework to protect children from violence in schools, there are still various challenges in its implementation. Further efforts are needed to increase awareness, reporting, and law enforcement related to cases of violence against children in schools by the government, including the establishment of more specific guidelines for child protection against violence in the school context and enhancing facilities and supervision through the improvement of teaching staff and special guidelines for all In Indonesia, concerning the procedures that schools should follow, the community, and parents in addressing violence that occurs in the school environment.